Legal Consequences of Making a Deed of Marriage Agreement by a Notary Who Has Not Been Registered - Manullang, Lasmaria; Sudiro, Amad (JURNAL USM LAW REVIEW, 2023)
This research aims to discover the legal consequences of making a marriage agreement deed by a notary who has yet to be registered at the Office of Religious Affairs. This research method is normative legal research examining the legal consequences of making a marriage agreement deed by a notary who has yet registered at the Office of Religious Affairs. The research method used includes research on legal principles, systematic law analysis, and legal synchronization study. This research is focused on case studies of the East Jakarta Religious Court Decision Number 4855/Pdt.G/2019/Pa. It is related to doing a marriage agreement deed by a notary without registration at the Office of Religious Affairs. The results of this study analyze the legal implications of non-recording, both from the perspective of the validity of the marriage agreement certificate and its legal impact on the parties concerned. The novelty of this research is that administrative inaccuracies in making a marriage agreement can affect its legal validity and related rights. This research also seeks to provide recommendations for increasing awareness and compliance with applicable legal procedures to avoid potential conflicts and disputes in the future related to the marriage agreement deed.